2000
DOI: 10.1562/0031-8655(2000)072<0028:arpfcv>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium Probe for Cell Viability Measurement Using Flow Cytometry, Confocal Microscopy and Time-resolved Luminescence¶

Abstract: The capability of the new luminescent probe (dibenzo[h,j] dipyrido[3,2-a:2',3'-c]phenazine)bis(2,2'-bipyridine)ruthenium(II) dication, (RB2Z), to discriminate live and dead cells has been tested on rat hepatocytes and mouse lymphocytes. RB2Z-stained cells were analyzed using flow cytometry, fluorescence (confocal) microscopy and time-resolved luminescence measurements. The established viability probes propidium iodide (PI) and SYTOX green (SG) were used as controls. The intense luminescence of RB2Z at 606 nm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Barton et al have recently shown the usefulness of this effect for studying the cellular uptake and nuclear localization of Ru(II) dppz complexes [3,4]. Similar complexes have also been used as probes for cell viability and nuclear staining [5,6]. We have previously shown that Ru(II) dppz complexes, made more hydrophobic by substitution with alkyl ether chains, are versatile as photophysical probes for phospholipid bilayers [7,8].…”
Section: Introductionmentioning
confidence: 96%
“…Barton et al have recently shown the usefulness of this effect for studying the cellular uptake and nuclear localization of Ru(II) dppz complexes [3,4]. Similar complexes have also been used as probes for cell viability and nuclear staining [5,6]. We have previously shown that Ru(II) dppz complexes, made more hydrophobic by substitution with alkyl ether chains, are versatile as photophysical probes for phospholipid bilayers [7,8].…”
Section: Introductionmentioning
confidence: 96%
“…Luminescence using viable cells was only detectable after addition of Triton X-100 as surfactant. It may therefore appear that 6 can not migrate across an intact fully functional cellular membrane, but is capable of binding to the nuclear DNA in dead cells or cells with damaged membranes [34]. The related dinuclear ruthenium 7 posesses an overall charge of 4+ and shows very high binding affinities to DNA, Fig.…”
Section: Cellular Uptake Of Oligopyridyl Com-plexesmentioning
confidence: 99%
“…The global tumbling of dimeric apoMb was accessible using ANS as probe (lifetime 15ns) but not by fluorescein, due to its short lifetime ( 3ns), and its local wobbling. The development of ruthenium derivatives [89,90] displaying longer lifetimes (from 400 to 700 ns) may contribute to improve the performance of fluorescence polarization experiments in crowding conditions. [56]), which appears as a residual anisotropy in the apoMb-Fl decays.…”
Section: Fluorescent Labeling Of Tracer Speciesmentioning
confidence: 99%